Analysis of communication of Islamic organizations in handling interpersonal conflicts - Hasibuan, Effiati Juliana (Penerbit Universiti Kebangsaan Malaysia, 2020)
The complexity of conflict increases as organizations become more open and diverse. Interpersonal conflict is a conflict that occurs between two or more individuals who work together in groups or teams. This is a conflict that occurs between two or more individuals. Many individual differences lead to interpersonal conflict, including personality, culture, attitudes, values, perceptions, and other differences. The purpose of this paper is to identify Islamic communication patterns in efforts to handle internal organizational conflicts. The methodology of this research uses a literature study using books and literature as the main object. This type of research provides a clear, objective, systematic, analytical, and critical description and information regarding communication strategies in dealing with internal conflicts contained in the Qur'an. These research findings that individual differences in goals, expectations, values, proposed actions, and suggestions on the best way to handle a situation cannot be avoided. Interpersonal conflict handling basically teaches organizational members to be able to handle interpersonal conflicts in various situations effectively and set the right mechanism so that unresolved problems are handled properly. One of the efforts to deal with this is the pattern of Islamic Communication based on Islamic sharia guidelines in terms of morality. So, this results paper concluded that in principle, in preventing and reducing the risk of conflict between organizations can be done with the principles of Islamic communication as explained in the Koran such as Tabayun, Tahkim, Al Syura, Al Afwu, and Al Ishlah. The Implication of this paper hope conflicts that can be handled well will only produce constructive results. Conflict and its resolution have an important role in private, public, and political organizations, as well as in judicial and employment disputes, in military operations and many other institutions.